Top management commitment towards quality management in the context of Malaysian construction organizations - Tan, Chin Keng; Abdul Rahman, Hamzah (2008)
Top management commitment towards quality management is generally perceived as one of the key factors in determining its success. It has been observed that the local construction industry is facing a lot of quality issues. In relation to this, the authors are trying to perceive quality management in the context of Malaysian construction industry from the perspective of top management commitment. The research aims to identify the constructs of commitment from literatures and explore the top management commitment towards quality management in building construction projects based on the constructs identified in the context of Malaysian construction organizations. Survey samples were drawn from the construction organizations of G5, G6, and G7 registered with the Construction Industry Development Board (CIDB) Malaysia. Research findings show that the top management of construction organizations is generally committed to quality management implementation from the perspectives of quality goals, efforts, involvement and attitude to change. Nevertheless, there are some areas which need to be improved. Firstly, quality is still lacking in terms of its importance in the mentality of the top management compared to cost and time and secondly, resources allocation should be further increased to a more satisfactory level.